Persepsi Petani Padi terhadap Layanan Irigasi di Daerah Istimewa Yogyakarta - Triyono Triyono; Nur Rahmawati; Bambang Heri Isnawan (AGRARIS: Journal of Agribusiness and Rural Development Research, 2019)
Improvement of agricultural resource management systems, especially irrigation water, is important in determining sustainable agriculture. This study aims to describe the quality of irrigation services on rice farming as well as its corelation to the farmers Willingness To Pay (WTP) irrigation services. The study was conducted in rice farming centers namely Sleman and Bantul Regency based on irrigation river flows that crossed the region. Respondents were taken from each irrigation area as many as 5 farmers using simple random sampling with total number of samples were 125 farmers.The irrigation service data and farmers Willingness To Pay irrigation services were analyzed using rank Spearman correlation to see the corelation of both factors. The result showed that there was a negative correlation between irrigation services and farmers Willingness To Pay irrigation fees., In general, rice farming irrigation services in Special Region of Yogyakarta are in good category, however willingness of farmers to pay irrigation services (WTP) is low. In order to support the sustainability of longterm irrigation services, it requires public awareness, especially farmers in irrigation utilization and the provision of smart irrigation control in irrigation maintenance.